Kinematic reliability evaluation of high-precision planar mechanisms experiencing non-uniform wear in revolute joints. (15th April 2022) - Zhuang, Xinchen; Yu, Tianxiang; Liu, Jingyi; Song, Bifeng
Highlights: A more practical wear prediction model for revolute joints is proposed. The wear test is conducted to verify the proposed wear prediction method. Slicing sampling is used to generate clearance samples with irregular boundary. Kinematic reliability method considering non-uniform joint clearance is developed. Abstract: Joint clearance significantly influences the motion accuracy of a mechanism. Most of the existing studies assumed that the clearance is regular with constant size. The effect of irregular joint clearance due to wear on the kinematic accuracy is ignored. Hence, this study conducts kinematic reliability analysis of high-precision planar mechanisms experiencing non-uniform wear. Firstly, under the framework of multi-body dynamics, an efficient wear prediction method based on Archard's wear model is presented for parameterized description of the clearance boundary. Secondly, fractional moments of the motion output considering the uncertainties of driving actuators, link dimensions and non-uniform joint clearance are derived with the dimension reduction method. On this basis, the maximum entropy model constrained by fractional moments is employed to approximate the distribution of the motion output. Then the kinematic reliability is accordingly calculated using the numerical integral. Meanwhile, a Monte Carlo simulation (MCS) based method is developed for kinematic reliability analysis by virtue of slicing sampling technique to provide a reference solution. Finally, experimental testing of a slider-crank mechanism is presented to verify the wear prediction method. The slider-crank mechanism is also used to demonstrate the effectiveness of the proposed kinematic reliability evaluation method.